Asset Management and Corporate Business Model of Naresuan University when Transformed into an Autonomous University - Danchaloenkijkul, Aphinankit (Journal of Modern Learning Development, 2022)
This purpose of this is to describe as a university under the control of the Ministry of Higher Education, Science, Research and Innovation, and is enttled to earn and control income from (1) benefits, fees, fines and service fees of the university, (2) money and assets donated to the University, (3) income or benefits derived from the use of State property, and (4) other income or benefits, without these earning being submitted to the Ministry of Finance. As a state-directed autonomous university, will need to seek more income from external sources and earn sufficient income to ensure its survival, in accordance with the government’s intentions and expectations that universities will be able to raise funds themselves without burdening the government with the requirement to allocate funds from the national budget. The university’s budget will be subsidized by a minimum 30% of the university’s annual budget, but no more than 50% of the university’s total budget in each year. Therefore, the existing assets in the university must be managed most advantageously and income in different forms to the university must be acquired appropriately and in accordance with the normal and proper expectations of the university context, and which does not contravene any other applicable laws, thereby enabling universities to reduce their reliance on public budgets and reduce the impact of university budgets on the the country’s economy. The authors of the article took examples of asset management and revenue provision in various forms at other universities that operate in the same manner as is proposed for Naresuan University. Rajabhat University is an example of a university that retains its status as a government office and which also has the task of seeking income from external sources. The article also addresses the requirement for Naresuan University to establish a Holding Company as an important legal entity to properly support the state-directed university revenue management process and that ensues that all other laws currently in force are not contravened in any manner, and the author present organization structure for example in the management of the organization.